PaxlovidTM Information From FDA and Guidance for AES Members. Issue 3 (June 2022) - Cokley, Jon A.; Gidal, Barry E.; Keller, Joy A.; Vossler, David G.; ,
This American Epilepsy Society (AES) official statement provides information and preliminary guidance to Society members related to the U.S. Food & Drug Administration (FDA) December 22, 2021 Emergency Use Authorization for Paxlovid™ for the oral treatment of mild to moderate COVID-19 in adults and children (≥12 years and weighing ≥40 kg). Paxlovid is likely to be widely prescribed, and important considerations for patients on antiseizure medications (ASMs) include key contraindications and potential toxicity or dose adjustments while taking Paxlovid. This statement highlights concerns and provides information about their pharmacologic basis. Of particular concern, concomitant use of Paxlovid with the ASMs carbamazepine, phenobarbital, phenytoin, and primidone is contraindicated, because they are strong inducers of the CYP3A4 isozyme that metabolizes Paxlovid and thereby could cause loss of virologic response and development of resistance. Alternate oral or intravenous COVID-19 treatments should be considered. A second concern is that Paxlovid may increase the plasma concentrations of many ASMs, because it inhibits the CYP3A4 isozyme. ASMs that are metabolized, at least in part, by CYP3A4 include cannabidiol, carbamazepine, clobazam, clonazepam, diazepam, ethosuximide, everolimus, felbamate, lacosamide, midazolam, oxcarbazepine, perampanel, stiripentol, tiagabine, and zonisamide. Patients receiving these medications may warrant closer monitoring while being treated with Paxlovid.